Save peraugantis tapatumas Alison Louise Kennedy kūriniuose Tai aš džiaugiuosi ir Pirminė palaima - Kačkutė, Eglė (Literatūra, 2009)
he paper focuses on the problem of identity in A. L. Kennedy’s novel So I’m Glad and the short storyOriginal Bliss. It argues that the structure of identity in the aforementioned works partly accounts for the ethics advanced in Kennedy’s work. At the centre of each work there is a romantically involved couple whose love stories offer interesting examples of a relationship between self and other. Kačkutė believes that the other in Kennedy‘s writing is peculiarly positioned neither in or outside the subject, it corresponds to Judith Butler’s idea of the constitutive outside that is brewed inside the subject. Either way such dialectics of the self and other results in a positive identity development. Such change is marked by traumatic and physically painful experiences, but results in a cathartic moment that suggests the profound ethics underlying Kennedy‘s artistic project.